A pilot study of early onset obsessive-compulsive disorder: Symptom dimensions and association analysis with polymorphisms of the serotonin transporter gene. (October 2018) - Kenezloi, Eszter; Lakatos, Krisztina; Horvath, Erzsebet Zsofia; Sasvari-Szekely, Maria; Nemoda, Zsofia
Highlights: A nominally significant difference was observed in the genotype frequencies of the serotonin transporter gene promoter polymorphisms (5-HTLPR) when using the S (short) and L (long) allele system in early onset obsessive compulsive disorder. Taking into consideration the later discovered functional rs25531, the difference between OCD cases and controls (from general population) was not significant using the triallelic 5-HTTLPR system. Using principle component analysis, a four factor structure emerged explaining 62.7% of the variance: (1) aggressive, somatic, religious, symmetry obsessions, and checking compulsions, (2) hoarding obsessions with hoarding, repeating, ordering, counting symptoms, (3) contamination, cleaning factor and (4) sexual thoughts. None of the assayed serotonin transporter gene polymorphisms showed significant association with the obtained factors. Abstract: Our aim was to introduce more homogenous phenotypes for studying genetic variations in the clinically heterogeneous obsessive compulsive disorder (OCD) beside classical case-control analysis. Symptoms were assessed with Children's Yale-Brown Obsessive Compulsive Scale (CY-BOCS), and principle component analysis of the lifetime symptom categories yielded four factors (Cleaning, Obsessive, Compulsive, Sexual). The comparison of serotonin transporter linked polymorphic region (5-HTTLPR) in 102 OCD patients and 223 controls showed an increased L-allele frequency but no difference was observed when rs25531 was included. Intronic variants of the serotonin transporter gene did not show association with either OCD, nor with the obtained factors.